Evaluación de polipirrol dopado con compuestos tipo porfirina para la aplicación en supercapacitores (2020)
Polypyrrole (PPy) films were synthesized with some dopants like p-toluenesulfonic acid (PTSA), 5,10,15,20-tetrakis (4-sulfonatophenyl)porphyrin (TPPS) and coordination complex ZnTPPS. The synthesis was performed by a galvanostatic pulse method on a glassy carbon electrode in aqueous solutions. The compounds TPPS and ZnTPPS were synthesized and characterized by means of melting point and magnetic resonance spectroscopy (NMR: 1H, 13C). The polymers PPy/PTSA, PPy/PTSA/TPPS, and PPy/PTSA/ZnTPPS were evaluated with cyclic voltammetry, galvanostatic charge/discharge cycles, electrochemical impedance spectroscopy, and SEM. The polymer with ZnTPPS did not show a capacitive material behavior, unlike the polymer with TPPS that its structure is highly porous with a specific capacitance of 250 F/g calculated from the galvanostatic charge/discharge in 1 M KCl solution at a current density of 0.5 A/g, with capacitance retention of 88% after 1000 cycles.